Atrial fibrillation in a pediatric patient caused by an unusual malignant etiology: A case report - Hubrechts, Jelena; Vô, Christophe; Boulanger, Cécile; Carkeek, Katherine; Moniotte, Stéphane (Frontiers in Pediatrics, 2023)
This case report describes a 15-year-old patient with a known congenital malformation syndrome and immune deficiency, presenting with new-onset atrial fibrillation (AF) after a recent diagnosis of an intrathoracic mass. Transthoracic echocardiography showed a structurally and functionally normal heart and work-up confirmed a primary diffuse large B-cell lymphoma, with pericardial and left atrial involvement on cardiac magnetic resonance imaging. Electrical cardioversion was successfully performed to convert the AF and chemotherapy was promptly started. Antiarrhythmic treatment was continued for 6 weeks, without recurrent AF. We discuss the pathogenesis of AF in the setting of malignancies as well as the management strategies of AF, mainly based on adult guidelines.